How generalization relates to the exploration-exploitation tradeoff - Houser, Troy M. (Frontiers in Cognition, 2023)
It is known that animals foraging in the wild must balance their levels of exploitation and exploration so as to maximize resource consumption. This usually manifests as an arearestricted search strategy, such that animals tend to exploit environmental patches and make long excursions between patches. This optimal foraging strategy, however, relies on an underlying assumption: nearby locations yield similar resources. Here, we offer an explanation as to how animals utilize this assumption, which implicitly involves generalization. We also describe the computational mechanisms hypothesized to incorporate factors of exploitation, exploration, and generalization, thus, providing a more holistic picture of animal search strategies. Moreover, we connect this foraging behavior to cognition in general. As such, we suggest that cognitive processes, particularly those involved in sequential decision-making, reuse the computational principles grafted into neural activity by the evolution of optimal foraging. We speculate as to what neurobiological substrates may be using area-restricted search, as well as how a model of exploitation, exploration, and generalization can inform psychopathology.